PVHL is a regulator of glucose metabolism and insulin secretion in pancreatic beta cells. - Zehetner, J; Danzer, C; Collins, S; Eckhardt, K; Gerber, P; Ballschmieter, P; Galvanovskis, J; Shimomura, K; Ashcroft, F; Thorens, B; Rorsman, P; Krek, W (2008)
Insulin secretion from pancreatic beta cells is stimulated by glucose metabolism. However, the relative importance of metabolizing glucose via mitochondrial oxidative phosphorylation versus glycolysis for insulin secretion remains unclear. von Hippel-Lindau (VHL) tumor suppressor protein, pVHL, negatively regulates hypoxia-inducible factor HIF1alpha, a transcription factor implicated in promoting a glycolytic form of metabolism. Here we report a central role for the pVHL-HIF1alpha pathway in the control of beta-cell glucose utilization, insulin secretion, and glucose homeostasis. Conditional inactivation of Vhlh in beta cells promoted a diversion of glucose away from mitochondria into lactate production, causing cells to produce high levels of glycolytically derived ATP and to secrete elevated levels of insulin at low glucose concentrations. Vhlh-deficient mice exhibited diminished glucose-stimulated changes in cytoplasmic Ca(2+) concentration, electrical activity, and insulin secretion, which culminate in impaired systemic glucose tolerance. Importantly, combined deletion of Vhlh and Hif1alpha rescued these phenotypes, implying that they are the result of HIF1alpha activation. Together, these results identify pVHL and HIF1alpha as key regulators of insulin secretion from pancreatic beta cells. They further suggest that changes in the metabolic strategy of glucose metabolism in beta cells have profound effects on whole-body glucose homeostasis.